2021
DOI: 10.3390/ijerph18063214
|View full text |Cite
|
Sign up to set email alerts
|

Community Use of Face Masks against the Spread of COVID-19

Abstract: The role of face masks to prevent and control COVID-19 is critical, especially since asymptomatic or pre-symptomatic infected individuals can shed high loads of SARS-CoV-2 in the surrounding environment. In addition to being a two-way barrier to protect against virions droplets both in terms of “source control” (for the benefits of the community) and “physical protection” (for wearer), face masks also allow maintaining physiological temperatures and humidity of the nasal cavity and mouth, independently from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…Primary preventive measures include wearing masks that cover the mouth and nose, regular hand washing, using hand sanitizers, and physical distancing [ 3 , 4 ]. During the first wave of the COVID-19 epidemic in Israel, the Israeli Ministry of Health (MOH) issued guidelines for HCWs.…”
Section: Introductionmentioning
confidence: 99%
“…Primary preventive measures include wearing masks that cover the mouth and nose, regular hand washing, using hand sanitizers, and physical distancing [ 3 , 4 ]. During the first wave of the COVID-19 epidemic in Israel, the Israeli Ministry of Health (MOH) issued guidelines for HCWs.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that outdoor mass gatherings have a lower risk of transmission than indoor ones, because respiratory aerosols dissipate outdoors, and the risk may be reduced even more by mask wearing [ 49 ]. The role of face masks outdoor not only acts as a physical barrier against SARS-CoV-2 but also maintains the temperature of the upper respiratory tract in cold environmental outdoor conditions, thus supporting the innate immune system of upper airways against pathogen threats, and there is increased evidence of the effectiveness of mask use in indoor settings for prevention of SARS-CoV-2 infection [ 22 , 50 ]. Protests also occurred in summer in Europe and America, and winter in Australia, where winters are mild.…”
Section: Discussionmentioning
confidence: 99%
“…Despite parents’ initial concern about the possible harmful effects of wearing a face mask, studies have shown that both ventilation and oxygen intake have not been negatively affected [ 22 ]. The face mask covers the lower part of the face [ 23 ], including the teeth and, implicitly, the orthodontic appliances. Wearing a face mask could cause frustration due to the fact that the orthodontic appliances are no longer visible, as it is known that orthodontic appliances are often perceived as an elective luxury [ 24 ], and for children, the possibility of using colored elastic ligatures is one of the most appealing aspects during the orthodontic treatment [ 25 ].…”
Section: Introductionmentioning
confidence: 99%